LATIS: Comparing Galaxy and IGM Tomography Maps as Tracers of Large-scale Structure and Protoclusters at z ∼ 2.5 - Andrew B. Newman; Nima Chartab; Mahdi Qezlou; Gwen C. Rudie; Guillermo A. Blanc; Daniel D. Kelson; Simeon Bird; Caitlin Casey; Enrico Congiu; Olga Cucciati; Denise Hung; Brian C. Lemaux; et al. (The Astrophysical Journal)
We investigate the consistency of intergalactic medium (IGM) tomography and galaxy surveys as tracers of the cosmic web and protoclusters at z  ∼ 2.5. We use maps from the Ly α Tomography IMACS Survey (LATIS), which trace the distributions of Lyman-break galaxies (LBGs) and IGM Ly α absorption on ≃4 h ^−1 cMpc scales within the same large volume. Overall, the joint distribution of IGM absorption and LBG density is well constrained and accurately described by a simple physical model. However, we identify several exceptional locations exhibiting strong IGM absorption indicative of a massive protocluster, yet no coincident overdensity of LBGs. As discussed by Newman et al., whose results we revise using the complete LATIS survey data, these are candidate ultraviolet (UV)-dim protoclusters that may harbor distinct galaxy populations missed by rest-UV spectroscopic surveys. We present follow-up observations targeting one such candidate embedded within Antu, an extended region of IGM absorption at z = 2.685 that contains five IGM-selected protoclusters and has a total mass of 3 × 10 ^15 M _⊙ . Ly α emitters trace the overall structure of Antu but avoid the center of the candidate UV-dim protocluster, which also appears to contain no submillimeter-selected sources. A near-infrared spectroscopic galaxy census is needed to determine whether this large region is dominated by galaxies with reduced or absent star formation activity. This work adds to a growing and puzzling literature on discrepancies among different galaxy and IGM tracers, whose resolution promises to shed light on the early stages of environment-dependent galaxy evolution.